Modulation in Nutritional Quality of Microalgae, Chaetoceros calcitrans in Different Culture Media - K.P., Lincymol; Ittoop, Gijo; P., Lakshmi Devi; Joseph, Aneykutty (Fishery Technology, 2025)
The present study was initiated to identify the best medium for culture of Chaetoceros calcitrans that could provide better protein and lipid content while supporting good growth of the algae. The media selected were Walne’s, Miquel’s, Chu and f/2 media. The algae cultured in Walne’s, Miquel’s and f/2 media showed significantly higher content of lipid (P